An updated cost-effectiveness analysis of pneumococcal conjugate vaccine among children in Thailand - Piyameth Dilokthornsakul (2019)
© 2019 Elsevier Ltd Background: A previous cost-effectiveness analysis (CEA) showed that Pneumococcal Conjugate Vaccine (PCV) 10 and PCV13 were not cost-effective for universal immunization among children in Thailand. Given recent changes in the evidence of efficacy, herd effects and price, a CEA of PCVs should be revisited. This study aimed to determine the cost-effectiveness of PCV10 and PCV13 compared to no PCV vaccination in Thai children. Material and methods: A Markov model was developed under a societal perspective with a lifetime horizon. Inputs were derived from a comprehensive literature review. Costs were calculated using the Thai National Electronic Database and converted to the year 2017 value. All costs and outcomes were discounted at a rate of 3%. The findings were reported as incremental cost-effectiveness ratios (ICERs) in Thai Baht (THB) per quality-adjusted life year (QALY) gained. Sensitivity analyses were performed. A cost-effectiveness acceptability curve was generated with the cost-effectiveness threshold of 160,000 THB/QALY. Results: Base-case analysis of 2 + 1 dose schedule and five-year protection, with no consideration of herd effect showed that ICER for PCV10 was 170,437 THB/QALY, while ICER for PCV13 was 73,674 THB/QALY. With consideration of herd effect, both PCV10 and PCV13 had lower costs and higher QALYs compared to no PCV vaccination. Based on our probabilistic sensitivity analysis at willingness-to-pay of 160,000 THB/QALY, PCV13 had 93% of being cost-effective, while 4.7% and 2.3%, for PCV10 and no PCV vaccination, respectively. Conclusion: At current prices, PCV13 is cost-effective, while PCV10 is not cost-effective in Thailand. When considering herd-effect, both PCV10 and PCV13 are cost-effective.